Developing PBL To Improve Mathematical Problem Solving And Self Efficacy - Fransisca Anggalia; Haninda Bharata; Undang Rosidin (SAINTIS Publishing, 2020)
This study is a research development (RD) that aims to find out developing Problem-Based Learning (PBL) to improve students' mathematical problem solving abilities and valid, practical and effective student self-efficacy. The procedure of this research uses research development by Borg gall, Research and Information Collecting, Planning, Developing Preliminary of Products, Preliminary Testing ,Main Product Revision, Main Field Test, Operational Product Revision, Operational Field Testing, Final Product Revision, Dissemination and Implementation, but in this study it was carried out only to the sixth stage. Data collection techniques using observation, interviews, questionnaires, and tests. The design is validated by the learning model design expert, while the learning device is validated by the material expert, media expert and education practitioner. Furthermore the design was revised according to expert opinion. It was concluded that the ability to solve mathematical problems and self efficacy with problem based learning is more effective than the ability to solve mathematical problems with conventional learning.